Correction: Can the digital economy contribute to rural revitalization? A case of from China? - Yuanquan Lu; Yuan Meng; Li Chen; Yuan Zhang (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0310313.].